Step
*
1
of Lemma
select-from-upto
.....assertion..... 
∀d:ℕ. ∀n,m:ℤ.  (((m - n) ≤ d) 
⇒ (∀k:ℕm - n. ([n, m)[k] ~ n + k)))
BY
{ ((InductionOnNat THENA Auto) THEN (UnivCD THENA Auto)) }
1
1. d : ℤ
2. n : ℤ
3. m : ℤ
4. (m - n) ≤ 0
5. k : ℕm - n
⊢ [n, m)[k] ~ n + k
2
1. d : ℤ
2. 0 < d
3. ∀n,m:ℤ.  (((m - n) ≤ (d - 1)) 
⇒ (∀k:ℕm - n. ([n, m)[k] ~ n + k)))
4. n : ℤ
5. m : ℤ
6. (m - n) ≤ d
7. k : ℕm - n
⊢ [n, m)[k] ~ n + k
Latex:
Latex:
.....assertion..... 
\mforall{}d:\mBbbN{}.  \mforall{}n,m:\mBbbZ{}.    (((m  -  n)  \mleq{}  d)  {}\mRightarrow{}  (\mforall{}k:\mBbbN{}m  -  n.  ([n,  m)[k]  \msim{}  n  +  k)))
By
Latex:
((InductionOnNat  THENA  Auto)  THEN  (UnivCD  THENA  Auto))
Home
Index